Tricuspid annular plane systolic excursion (TAPSE) in chronic obstructive pulmonary disease patients: a systematic review and meta-analysis - Maria Groussis; Quincy K. Tran; Megan Hoffer; Jalil Ahari; Ali Pourmand (Clinical and Experimental Emergency Medicine)
Objective Tricuspid annular plane systolic excursion (TAPSE) is an echocardiographic parameter that serves as a prognostic indicator for the severity of chronic obstructive pulmonary disease (COPD) clinical course. This study, consisting of a systematic review and meta-analysis, evaluates the current literature to elucidate the relationship between TAPSE measurement in COPD patients versus control subjects to discern baseline evidence of right heart strain. Methods PubMed, Scopus, CINAHL, Web of Science, and Cochrane Library databases were searched from their beginnings through November 1, 2023, for eligible studies. Outcomes included the difference of TAPSE measurement and right ventricular (RV) wall thickness between COPD patients and control patients. The Newcastle-Ottawa Scale was applied to assess risk of bias, Q-statistics and I2 values were used to assess for heterogeneity, and Egger and Begg tests were used to assess publication bias. Results The search yielded 11 studies reporting TAPSE values involving 1,671 patients, 800 (47.9%) of which had COPD. The unadjusted mean TAPSE value for COPD patients was 18.9±4.0 mm, while the mean TAPSE value for control patients was 22.2±0.8 mm. The presence of COPD was significantly associated with decreased TAPSE values, with the meta-analysis reporting the mean difference in TAPSE value at –3.0 (95% confidence interval, –4.3 to –1.7; P=0.001) between COPD and control patients. Six studies reported the RV free wall thickness [19,21,22,26–28]. The unadjusted mean RV free wall thickness for COPD patients was 4.9±1.2 mm, and for control patients was 3.4±0.7 mm. Conclusion This meta-analysis demonstrated statistically significant lower TAPSE values and thicker RV free wall among COPD patients as compared with control patients.